Exploratory Research on Quantitative Parameters of Sheng’s Acupuncture and Moxibustion Technique based on Wearable Acupuncture Pressure Sensor - Zhou, Jipeng; Sheng, Yan; Wang, Yu; Zhang, Cong; Sheng, Canruo; Liu, Lanying (Journal of Contemporary Medical Practice, 2025)
Objective: To investigate and analyze the unique needling technique characteristics of Sheng’s by acquisition of quantitative parameters of needling technique based on a wearable needling pressure sensor device. Methods: The wearable acupuncture pressure sensor device and the matching acupuncture technique acquisition system were used to collect the lifting and insertion pressures on acupuncture needles, twisting moments, and finger pressures on needle handles during bilateral ChiZe (LU5) acupoint acupuncture in 30 subjects by Sheng’s acupuncture technique inheritance and acupuncture clinicians, and the characteristics of their techniques were analyzed and compared. Results: Sheng’s acupuncture technique downward insertion pressure, twisting torque and lifting insertion frequency parameters were significantly greater than those of the acupuncture clinician’s(P<0.05). Thumb and index finger pressure and force application frequency parameters were significantly greater than acupuncture clinician’s (P<0.001). Middle finger pressure and frequency of force application were significantly less than the finger force application parameters of acupuncture clinician(P<0.05). Conclusion: Based on wearable needling pressure sensor device and needling technique acquisition system can objectively and stably represent doctors’ needling techniques and embody the characteristics of different needling techniques. It is initially believed that Sheng’s needling technique is characterized by heavy insertion and deep stabbing after needle entry, rapid twisting, greater finger force of the thumb and index finger, and faster frequency of force application. It can provide a data-based and visualized objective basis for further exploring the characteristics of acupuncture techniques of famous veteran Chinese medicine practitioners and the inheritance of Sheng’s acupuncture techniques.